2017
DOI: 10.1002/smj.2728
|View full text |Cite
|
Sign up to set email alerts
|

Connecting and creating: tertius iungens, individual creativity, and strategic decision processes

Abstract: Research Summary: In contrast to previous research that emphasized macro-to-macro relationships, this study investigates how strategic decision characteristics shape the creative process at the organizational micro-level. Whereas individual creativity thrives on novel combinations of diverse knowledge and perspectives, we argue that the characteristics of strategic decisions influence the extent to which employees' combinatory activities enhance their creativity. Multilevel modeling results based on 638 employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 124 publications
(227 reference statements)
0
28
0
Order By: Relevance
“…These findings by Kaplan et al (2017) and emphasize the need to consider not only the effects of brokering on idea generation but also the longer term consequences of brokering for the utilization and adoption of the products that result from brokered collaborations (i.e., the transition from creativity to innovation; cf. Kauppila, Bizzi, & Obstfeld, 2018).…”
Section: Helpful Brokersmentioning
confidence: 99%
“…These findings by Kaplan et al (2017) and emphasize the need to consider not only the effects of brokering on idea generation but also the longer term consequences of brokering for the utilization and adoption of the products that result from brokered collaborations (i.e., the transition from creativity to innovation; cf. Kauppila, Bizzi, & Obstfeld, 2018).…”
Section: Helpful Brokersmentioning
confidence: 99%
“…It is observed that groups on the whole are able to produce a larger variety of ideas than individuals, specifically face-to-face groups more than computermediated groups and smaller groups rather than individuals, showing significantly better preparation and incubation of ideas, respectively leading to more creative satisfaction among face-to-face group members (Kristensson & Norlander, 2003). Further, individuals who collaborate with, and bring together diverse ideas of people in their network tend to improve their own creative performance (Kauppila, Bizzi & Obstfeld, 2018). Hence, when we train students in creative thinking, we encourage them to work in groups and even form dyadicrelationships in teams, since, among team characteristics, high quality, dyadic co-worker relationships lead to the establishment of more favourable creative team environments (Bornay-Barrachina & Herrero, 2018).…”
Section: Creating Rules Of Engagement For Team Members In a Classroommentioning
confidence: 99%
“…We focused on the effects of trait anxiety and competition shadow because, compared to other emotions, anxiety and competition shadow are more associated with uncertainty ( Calvo & Dolores Castillo, 2001 ; Grupe & Nitschke, 2013 ), which is inherent in the decision to anchor a reference point. We set the individual as the unit of analysis because individuals often establish and manage new ventures ( Sarason et al, 2006 ), and make many significant estimations about known and unknown rivals ( Kauppila et al, 2018 ). This research has focused on the individual- rather than the group-level stimulus of rival estimation.…”
Section: Introductionmentioning
confidence: 99%